Local labor markets and taste-based discrimination - Clémence Berson (IZA Journal of Labor Economics, 2016)
This article appeals to heterogeneity in workers' non-wage preferences to model taste-based discrimination. Firms hire both types of workers and pay lower wages to minority workers, whatever their taste for discrimination. A single prejudiced firm in the market produces a substantial wage gap in all firms. Consequently, discrimination allows unprejudiced firms to make non-zero profits, so that they have little incentive to drive out prejudiced firms. As the market does not eliminate discrimination, state intervention is required. Indirect policies do not affect the absolute wage gap between the two groups, but may be more likely to be used than direct policies.
Keywords: J42; J71; L13; 330; Discrimination; Oligopsony; Wage gap